Effects of top female leaders on R&D activities under different executive pay gaps - Hui, Hu; Jianing, Hou; Yujing, Deng; Changzheng, Zhang (Journal of Accounting, Business and Finance Research, 2024)
Innovation is regarded as a crucial driver in achieving the vision of manufacturing power, and top female leaders play an increasingly important role in driving innovation. Based on a sample of 14,716 observations from Chinese manufacturing enterprises listed between 2010 and 2020, this study empirically examines the impact of top female leaders in different positions on (Research and Development) R&D intensity and investigates the moderating role of executive pay gap on this relationship. The results indicate that (1) female executive directors and female non-executive directors have a negative impact on R&D intensity, while female (Chief Finance Officer) CFO and female independent directors have a positive impact on R&D intensity, and there are no significant relationships between female supervisors, female (Chief Executive Officer) CEO, and female non-director executives and R&D intensity; (2) executive pay gap strengthens the negative effects of female executive directors and female non-executive directors on R&D intensity, weakens the negative effects of female CEO and female non-director executives on R&D intensity, and has no significant moderating role on the effects of female independent directors, female supervisors, and female CFO on R&D intensity.